The effects of magnesium supplementation on abnormal uterine bleeding, alopecia, quality of life, and acne in women with polycystic ovary syndrome: a randomized clinical trial - Mahsima Jaripur; Hatav Ghasemi-Tehrani; Gholamreza Askari; Mahsa Gholizadeh-Moghaddam; Cain C. T. Clark; Mohammad Hossein Rouhani (BMC, 2022)
Abstract Background Abnormal uterine bleeding (AUB), alopecia, low quality of life, and acne are considered as complications of polycystic ovary syndrome (PCOS). We hypothesized that magnesium supplementation would yield beneficial effects on PCOS related complications. Objective To examine the effects of magnesium supplementation on AUB, alopecia, quality of life, and acne. Methods In this parallel randomized clinical trial, we randomly assigned 64 women with PCOS to the magnesium group (n = 32) or placebo group (n = 32) for 10 weeks. AUB, alopecia, quality of life, and acne were assessed by the International Federation of Gynecology and Obstetrics criterion, the Sinclair Scale, the Health Survey Quality of Life Questionnaire, and the Global Acne Grading System, respectively. This randomized clinical trial was registered at IRCT.ir (IRCT20130903014551N9). Results Magnesium supplementation significantly improved the components of quality of life including physical functioning (p = 0.011), role limitations due to physical health (p = 0.012), role limitations due to emotional problems (p < 0.001), energy/fatigue (p = 0.005), emotional wellbeing (p < 0.001), social functioning (p = 0.002), general health (p = 0.013), and total quality of life (p < 0.001), compared with placebo. No significant effect was observed on acne, alopecia, and AUB. Conclusion Magnesium supplementation in women with PCOS had a significant positive effect on improving total quality of life. Trial registration This randomized clinical trial was registered at IRCT.ir on 2020-10-18 (Registration Code: IRCT20130903014551N9 ).